It's not just about pads! Adolescent reproductive health views in Kenya: A qualitative secondary analysis. - Sylvia Ayieko; Angela Nguku; Nancy Kidula (PLOS Global Public Health)
Many adolescents face barriers to accessing reproductive health care even though quality reproductive health care is a fundamental human right. The objective of this study is to understand the requests of quality reproductive health among high school girls in Kenya. We conducted a secondary analysis of qualitative data from a sub-sample of adolescent girls in Kenya who participated in the What Women Want global campaign and analyzed interview data from key informants involved in the survey. We used pre-existing codes and current literature to design the coding framework and thematic analysis to describe emerging themes. Atlas. ti 8 was used to organize and analyze codes. Over 4,500 high school girls, ages 12 and 19 years, were included in the analysis, with 61.6% from all-girls boarding schools and 13.8% from mixed-day schools. Data from nine key informants complemented findings from the survey. Emerging themes included: 1) The need for improved menstrual health and hygiene: Sanitary towels and cleaner toilets; 2) Prevention of adolescent pregnancy: Access to contraception; 3) Respect and dignity: Participants want privacy and confidentiality; and 4) The need to address social determinants of health: Economic stability and a safe physical environment. This study indicated that adolescent high school girls have varied requests for reproductive health care and services. While menstrual health and hygiene are key issues, reproductive needs are beyond just sanitary products. The results suggest a need for targeted reproductive health interventions using a multi-sectoral approach.